A COMPARATIVE STUDY OF RHETORICAL STRUCTURE OF SEVERAL THESIS ABSTRACTS BY UNDERGRADUATE STUDENTS OF UNIVERSITAS BENGKULU - Bayu Wijaya; Safnil Arsyad; Mei Hardiah; Elfrida (UNIB Press, 2023)
The abstract in every research paper has always served as an attention-grabber, either encouraging readers to continue reading the research or discouraging them from doing so. This research is aimed to find the most dominant move and step of thesis abstract by undergraduate students and to identify any differences. This research used a mix method approach. The design of this research is descriptive, using quantitative as well as qualitative data. The data was taken from thirty undergraduate thesis abstracts of Education faculty from University of Bengkulu who graduated between 2019 to 2022. Hyland’s five-move model will be used for research instrument. The result showed that, the majority and most dominant moves that found were Move 2 (purpose) 100%, followed by Move 3 (Method) 97%, Move 4 (Product) 97% and Move 5 (Conclusion) 80%, while the most dominant Step that found was Step 1 of Move 2 (Stating the purpose directly) 100%. Also, there is no significant differences of Move from the three study programs (English, Physic and Guidance and Counselling). Conclusion, most of the students were simply following the “Thesis Writing Guidelines” in writing their abstracts. Therefore, it would be better for the department in charge to revise the guidelines and use this research as a reference or guidance for a better abstract writing.